Exploiting signal processing approaches for broadband echosounders. (28th August 2017) - Lavery, Andone C.; Bassett, Christopher; Lawson, Gareth L.; Jech, J. Michael
Abstract: Broadband echosounders, which transmit frequency-modulated pulses, increase the spectral characterization of targets relative to narrowband echosounders, which typically transmit single-frequency pulses, and also increase the range resolution through broadband matched-filter signal processing approaches. However, the increased range resolution does not necessarily lead to improved detection and characterization of targets close to boundaries due to the presence of undesirable signal processing side lobes. The standard approach to mitigating the impact of processing side lobes is to transmit tapered signals, which has the consequence of also reducing spectral information. To address this, different broadband signal processing approaches are explored using data collected in a large tank with both a Kongsberg–Simrad EK80 scientific echosounder with a combination of single- and split-beam transducers with nominal centre frequencies of 18, 38, 70, 120, 200, and 333 kHz, and with a single-beam custom-built echosounder spanning the frequency band from 130 to 195 kHz. It is shown that improved detection and characterization of targets close to boundaries can be achieved by using modified replica signals in the matched filter processing. An additional benefit to using broadband echosounders involves exploiting the frequency dependence of the beam pattern to calibrate single-beam broadband echosounders using an off-axis calibration sphere.